Diagnosa Keperawatan Yang Sering Ditegakkan Perawat Pada Pasien Tuberkulosis Paru Di Rumah Sakit - Muhamad Rofii; Bambang Edi Warsito; Agus Santoso; Sarah Ulliya (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2018)
Tuberculosis is one of the biggest health problems in the world. This disease is also the highest cause of death and morbidity in developing countries, such as Indonesia. Most nurses do not carry out treatment plans for pulmonary tuberculosis patients because there is no standard structure even though there are guidelines for nursing management of pulmonary TB patients. The purpose of this study was to determine nursing diagnoses that are often enforced by nurses in pulmonary tuberculosis patients. The study was conducted in the inpatient hospital. This study used descriptive observational and descriptive explorative approaches. The samples were the documentation of the TB patients by using nonprobability sampling, namely purposive sampling saturation. Data analysis used univariate analysis with frequency distribution. The results of the study show that the formulation of nursing diagnosis is ineffective airway clearance(52%), the writing of 1 (one) diagnosis of ineffective airway clearance into 13 different diagnostic names. The nurse wrote the diagnosis of ineffective breathing patterns into 7 forms of diagnosis. Nurses also wrote diagnosis of acute pain into 5 forms of nursing diagnosis, and hyperthermy diagnosis into 2 forms of nursing diagnosis. The research recommendation is that hospital management is expected to improve nurses' skills in writing the latest nursing diagnoses, monitoring and evaluating both qualitatively and quantitatively Â in the writing of nursing diagnoses, applying the latest standards of nursing diagnoses. Nurses are expected to apply the latest nursing diagnoses in accordance with the use of NANDA.